DISCRETE EVENT SIMULATION MODELING WITH ARENA FOR COMBINATION OF MANUAL QUEUE AND FAST TRACK QUEUE IN HOSPITAL - Krisnawati, Febrian; Anugroho, Dhoni Muhamad Room; Rachmawati, Laura Yunita; Asrol, Muhammad (Jurnal PASTI (Penelitian dan Aplikasi Sistem dan Teknik Industri), 2022)
In this study an analysis of the patient queuing system will be carried out by developing a queuing system, namely adding aspects of patient registration status and the registration process with a system or machine or through the hospital’s web by downloading an application. This study aims to improve the efficiency of patient service management in clinics and develop a patient care management simulation model so that the number of patient rejections and patient waiting time in clinics. Discrete Event Simulation (DES) with ARENA and compare it with manual processes and with applications or machines in the registration process. The results show that patient rejection can be reduced to 1%, and the average patient time to be seen by a doctor is 0.7145 hours. If converted into minutes, each type of patient takes about 10 minutes in the doctor’s office.